2019
DOI: 10.1016/j.lungcan.2019.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of YS110, a recombinant humanized monoclonal antibody to CD26, in Japanese patients with advanced malignant pleural mesothelioma

Abstract: Objectives: CD26 is a transmembrane glycoprotein with dipeptidyl peptidase IV activity that is overexpressed in malignant pleural mesothelioma (MPM). We performed a phase I study to determine the maximum tolerated dose, pharmacokinetics, and antitumor activity of YS110, a monoclonal antibody to CD26, in Japanese patients with MPM intolerant of or refractory to prior standard therapies. Material and methods: The study was designed as an open-label, 3 + 3 dose-escalation, phase I trial. Patients were sequentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
3
12
1
Order By: Relevance
“…The expression levels of the transcripts of these CSC markers were similarly increased by rhIL‐1β stimulation (Figure 2B). Among these CSC markers, we focused on CD26, which has been recently reported to be clinically actionable by a novel monoclonal antibody, YS‐110 27 . Consistent with the results for the transcripts, flow cytometry analysis demonstrated that cell surface CD26 expression was upregulated in a time‐dependent manner by rhIL‐1β stimulation (Figure 2C).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…The expression levels of the transcripts of these CSC markers were similarly increased by rhIL‐1β stimulation (Figure 2B). Among these CSC markers, we focused on CD26, which has been recently reported to be clinically actionable by a novel monoclonal antibody, YS‐110 27 . Consistent with the results for the transcripts, flow cytometry analysis demonstrated that cell surface CD26 expression was upregulated in a time‐dependent manner by rhIL‐1β stimulation (Figure 2C).…”
Section: Resultssupporting
confidence: 77%
“…Among these CSC markers, we focused on CD26, which has been recently reported to be clinically actionable by a novel monoclonal antibody, YS-110. 27 Consistent with the results for the transcripts, flow cytometry analysis demonstrated that cell surface CD26 expression was upregulated in a time-dependent manner by rhIL-1β stimulation (Figure 2C). We further investigated the pathway involved in rhIL-1β-induced CD26 upregulation.…”
Section: Il-1β Promotes Sphere Formation Through Upregulation Of Cd26 In Mpm Cellssupporting
confidence: 86%
See 2 more Smart Citations
“…In terms of tumor response, four of seven patients had stable disease, while one achieved a partial response. This phase I trial showed that YS110 administration yielded promising antineoplastic outcome in advanced MPM while remaining relatively well-tolerated, similar to the FIH trial reported previously [26].…”
Section: Malignant Mesotheliomasupporting
confidence: 84%